Histopathological Evidence of Adventitial or Medial Injury Is a Strong Predictor of Restenosis During Directional Atherectomy for Peripheral Artery Disease. (October 2015) - Tarricone, Arthur; Ali, Ziad; Rajamanickam, Anitha; Gujja, Karthik; Kapur, Vishal; Purushothaman, K-Raman; Purushothaman, Meerarani; Vasquez, Miguel; Zalewski, Adrian; Parides, Micheal; Overbey, Jessica; Wiley, Jose; et al.
Purpose: To investigate the impact on restenosis rates of deep injury to the adventitial layer during directional atherectomy.Methods: Between 2007 and 2010, 116 consecutive patients (mean age 69.6 years; 56 men) with symptomatic femoropopliteal stenoses were treated with directional atherectomy at a single center. All patients had claudication and TASC A/B lesions in the superficial femoral or popliteal arteries. Histopathology analysis of atherectomy specimens was performed to identify adventitial injury. Clinical follow-up included physical examination and duplex ultrasound scans at 3, 6, and 12 months in all patients. The primary endpoint was the duplex-documented 1-year rate of restenosis, which was determined by a peak systolic velocity ratio <2.4. Patients were dichotomized by the presence or absence of adventitial or medial cuts as evaluated by histopathology.Results: Adventitial injury were identified in 62 (53%) of patients. There were no differences in baseline demographic and clinical features (p>0.05), lesion length (58.7±12.8 vs 56.2±13.6 mm, p=0.40), or vessel runoff (1.9±0.6 vs 2.0±0.6, p=0.37) between patients with and without adventitial injury, respectively. The overall 1-year incidence of restenosis was 57%, but the rate was significantly higher (p<0.0001) in patients with adventitial or medial injury (97%, 60/62) as compared with those without (11%, 6/54).Conclusion: Lack of adventitial injury after atherectomy for femoropopliteal stenosis is strongly related to patency at 1 year.